Long‐term health effects after resolution of acuteCryptosporidium parvuminfection: a 1‐year follow‐up of outbreak‐associated cases. Issue 11 (November 2017) - Stiff, Rhianwen E.; Davies, Angharad P.; Mason, Brendan W.; Hutchings, Hayley A.; Chalmers, Rachel M.
Abstract : Abstract : We describe a longitudinal study carried out in an adult outbreak‐associated cohort to investigate health effects, including post‐infectious irritable bowel syndrome, occurring after resolution of acute Cryptosporidium parvum infection. New symptoms self‐reported up to 12 months included: weight loss (31%), abdominal pain (38%), diarrhoea (33%), eye pain (9%), joint pain (33%), fatigue (22%) and symptoms consistent with irritable bowel syndrome (IBS) (28%). Two people were medically diagnosed with IBS. This study describes for the first time sequelae reported by patients up to 12 months after infection with C. parvum, which appear to be similar to those described with C. hominis.